Pengaruh Pengetahuan dan Kelelahan Pegawai Terhadap Kecelakaan Kerja di Proyek Lippo Thamrin Office Tower PT Wijaya Karya (Wika), Tahun 2017 - Adu Halim Tatroman; Herlina Herlina (STIKes Persada Husada Indonesia, 2018)
Occupational Safety and Health (K3) is a program created by workers and employers in an effort to prevent accidents caused by work by identifying the potential cause of accidents and occupational diseases and anticipatory action in the case of accidents and occupational diseases. Lack of employee knowledge and tired feeling at work can lead to work accidents. Objective To know the influence of knowledge and fatigue of employees to work accident at Project Lippo Thamrin Office Tower PT Wijaya Karya (Wika). The object of this research is Project Lippo Thamrin Office Tower PT Wijaya Karya (Wika). This research is an analytic research using quantitative approach by using questionnaire. Independent variables (characteristics: age, working hours, length of service, education) Knowledge and Fatigue. Dependent variable Accident work. The results obtained from this study that there is significant influence between Knowledge, p-value (0,000) Fatigue, p-value (0,000) Working Hours, p-value (0.004) and Length of Employment Period, (0,004) with Work Accident. Project Worker Lippo Thamrin Office Tower PT Wijaya Karya (Wika) is classified as less good in terms of knowledge, fatigue, working hours, and length ofservice.